2020
DOI: 10.1111/ans.16306
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric patient bleeding and pain outcomes following subtotal (tonsillotomy) and total tonsillectomy: a 10‐year consecutive, single surgeon series

Abstract: Background: Subtotal tonsil surgery (tonsillotomy) remains a controversial procedure. We aimed to document bleeding rates and return to normal activity for total versus subtotal tonsil surgery in the paediatric population. Methods: A 10-year cohort of 608 children from a single-surgeon series was analysed. Bleeding events were classified using the Flinders modification of the Stammberger criteria. Return to normal activity was defined as normal diet and return to childcare/school. Results: A total of 8.3% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…23 Another recent large cohort study (n = 608) noted similar overall revision surgery rates (2.4%), although it is worth noting that patients with recurrent tonsillitis were largely excluded from the ICT group initially. 24 This further demonstrates that those undergoing ICT for recurrent tonsillitis do not appear to have an additional risk of revision surgery.…”
Section: Comparison With Other Studiesmentioning
confidence: 84%
“…23 Another recent large cohort study (n = 608) noted similar overall revision surgery rates (2.4%), although it is worth noting that patients with recurrent tonsillitis were largely excluded from the ICT group initially. 24 This further demonstrates that those undergoing ICT for recurrent tonsillitis do not appear to have an additional risk of revision surgery.…”
Section: Comparison With Other Studiesmentioning
confidence: 84%
“…Attard and Carney, in their study of 608 paediatric patients, reported an 8.3 and 1.8 per cent post-operative haemorrhage rate for extracapsular tonsillectomy and intracapsular tonsillectomy, respectively. 23 Using a modification of Stammberger's grading system, they also evaluated degrees of bleeding and found, in addition to higher rates, a significantly greater severity of bleeds in the extracapsular tonsillectomy group compared with the intracapsular tonsillectomy cohort. 23 Similarly, Duarte et al found that 88.2 per cent of all postoperative haemorrhage occurred in their extracapsular tonsillectomy group compared with only 11.8 per cent who had undergone intracapsular tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…23 Using a modification of Stammberger's grading system, they also evaluated degrees of bleeding and found, in addition to higher rates, a significantly greater severity of bleeds in the extracapsular tonsillectomy group compared with the intracapsular tonsillectomy cohort. 23 Similarly, Duarte et al found that 88.2 per cent of all postoperative haemorrhage occurred in their extracapsular tonsillectomy group compared with only 11.8 per cent who had undergone intracapsular tonsillectomy. 24 The systematic review by Zhang et al demonstrated a 79 per cent reduction in secondary haemorrhage occurring in intracapsular tonsillectomy vs extracapsular tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review revealed that the recurrence rate after tonsillotomy was approximately 3%, younger children had a higher risk of recurrence, and the most common cause of reoperation was snoring. 16 , 17 , 19 Waldeyer’s ring is composed of numerous lymphoid follicles in the lamina propria of the pharyngeal mucosa, which integrates into adenoid lymphoid tissue and forms a ring. The lymphoid tissue in Waldeyer’s ring restricts the growth of tissue in both areas, so we often find after tonsillectomy combined with adenoidectomy that the cause of nasal obstruction and snoring is tonsillar hypertrophy of the eustachian tube.…”
Section: Discussionmentioning
confidence: 99%